(untitled) (ЕтноАнтропоЗум/EthnoAnthropoZoom, 2020)
In the ethnographic analysis of the Balkans, the traditional costume commonly represents a distinguishing feature of national identity, as well as an expression of the historical and cultural milieu of the peoples that live here. However, what happens when the ethnical and national identity of the costume transmogrifies into the cultural identity of a system and an era that, in turn, introduces changes to the traditional costume itself? This cultural and ethnographic transformation in different historical periods has been conditioned by various types of institutional interventions for discovering methods and forms, administered through legislative measures, even bans in order to provide legislative protection of such material cultural goods that belong to a certain people. In this case, by offering a chronological, historical overview, we describe the transformation of part of the clothing culture as an expression of a system such as the system that introduced the Law on Banning Niqabs and Burqas, published in the Official Journal of the Socialist Republic of Macedonia (no. 1, January 12, 1951). In a broader context, laws that do not consider clothing to be an expression of cultural diversity or national identity, but raise it as an issue for the society and the state, are enacted even today in a large number of European countries.